Acute Intestinal Intussusception: Beware of Burkitt's Lymphoma - Hind Sahli MD; Jihane El Mandour MD; Jihad Boularab MD; Nazik Allali PhD, MD; Latifa Chat PhD, MD; Siham El Haddad PhD, MD (SAGE Publishing, 2022)
Burkitt's lymphoma can show in a variety of ways, and it's frequently identified in children owing to the development of an abdominal tumor. This aggressive, fast growing tumor can induce either indirect symptoms due to pressure phenomena or direct involvement of the intestine lumen, resulting in intestinal obstruction or intussusception. We are reporting a case of intestinal intussusception in a patient with Burkitt's lymphoma.